Comparison of heat transfer in liquid and slush nitrogen by numerical simulation of cooling rates for French straws used for sperm cryopreservation - Sansiñena, Marina Julia (2011)
Fil: Sansiñena, Marina Julia. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina